Redescription of Ambrysus montandoni La Rivers, 1963 (Hemiptera: Heteroptera: Naucoridae), with the first records for Brazil - Rodrigues, Higor D. D.; de Melo, Alan Lane; Sites, Robert W. (Zootaxa, 2012)
The naucorid Ambrysus montandoni La Rivers is known from males collected from southern Venezuela. Presented here are aredescription of the male, original description of the female, illustrations of both sexes and genitalia, and the first records of the species from Brazil. Subgeneric associations in Ambrysus are discussed.